Wisdom of crowds: the effect of participant composition and contribution behavior on Wikipedia article quality. Issue 2 (15th January 2020) - Lin, Yan; Wang, Chenxi
Abstract : Purpose: This paper aims to explore the effect of participant composition and contribution behavior of the different types of participants on the quality of knowledge generation in online communities. Design/methodology/approach: This study samples all the featured articles in Chinese Wikipedia and performs a Cox regression to reveal how participant composition and contribution behavior affect the quality of articles in different contexts. Findings: The results show that an increase in the number of participants increases the possibility of either enhancing or reducing the article quality. In most cases, the greater the proportion of core members (people who frequently participate in editing), the higher the possibility of enhancing the article quality. Occasional participants' editorial behavior hinders quality promotion, this negative effect weakens when such editorial behavior becomes more frequent. Practical implications: The findings help to better leverage the role of online communities in practice and to achieve knowledge collaboration in a more efficient manner. For example, an appropriate centralized organizational form should be established in online communities to improve the efficiency of crowd contributions. And it is worth developing mechanism to encourage participants to frequently participate in editing the article. Originality/value: This study contributes to the research on the organizational forms of online communities by showing the effect of participant composition and behavior in the new form of organizing on knowledge generation. This study also contributes to the research on wisdom of crowds by revealing who in a group of participants, in what context, and by what means influence knowledge generation.